"دور وأهمية قرينة البراءة كأداة إثبات في المسائل الجنائية" (Comprehensive Journal of Science, 2026)
This research aims to clarify the importance of the presumption of innocence as a means of proof within the scope of criminal law. It relies on legal evidence and its effects according to the descriptive analytical approach, to demonstrate its judicial implications for the commitment to protecting individual rights and freedoms. This principle dictates that a person is presumed innocent unless proven otherwise by a conclusive judicial ruling issued by a competent legal court according to legal standards.
Keywords: presumption, criminal law, legal texts, punishment